Finnish banks' problem assets: Result of unfortunate asset structure of too rapid growth? - Heikki Solttila; Vesa Vihriälä (Bank of Finland, 1994)
The paper focuses on the proximate causes of the Finnish savings and cooperative banks' non-performing assets in the current banking crisis.Specifically, the effects of the lending structure at the outset of the crisis and the rate of growth of lending in the latter half of the 1980s are investigated.The main findings are: (1) Lending structure alone is not sufficient to explain the variation in the share of non-performing assets among the local banks.(2) Growth of lending is a major explanatory factor: the faster the growth in the second half of the 1980s, the higher the later share of non-performing assets.(3) Growth of lending is a particularly important "cause" in the case of the savings banks, where lending structure does not seem to have had much of an impact.(4) Lending to manufacturing, construction and trade has had a significant negative effect on the cooperative banks' asset quality.(5) Differences in the rate of lending growth go a long way in explaining why there are on average much more problem loans in the savings bank group than in the cooperative bank group.(6) The share of foreign currency loans is not an important factor when the effect of growth is accounted for, although the roles cannot be fully separated due to multicollinearity.(7) Assuming that growth of lending is more under the control of a bank than the structure of lending, the findings support the view that "bad luck" is not the only explanation of the Finnish banking problems but "bad banking" in the form of either ignorance of risks or deliberate risk taking is a major factor as well.
URN:NBN:fi:bof-20140807310
Keywords: 330